Second-Harmonic Generation in Resonant Nonlinear Metasurfaces Based on Lithium Niobate - Fedotova, Anna; Younesi, Mohammadreza; Sautter, Jürgen; Vaskin, Aleksandr; Löchner, Franz J.F; Steinert, Michael; Geiss, Reinhard; Pertsch, Thomas; Staude, Isabelle; Setzpfandt, Frank (Nano letters, 2020)
Lithium niobate is an excellent and widely used material for nonlinear frequency conversion due to its strong optical nonlinearity and broad transparency region. Here, we report the fabrication and experimental investigation of resonant nonlinear metasurfaces for second-harmonic generation based on thin-film lithium niobate. In the fabricated metasurfaces, we observe pronounced Mie-type resonances leading to enhanced second-harmonic generation in the direction normal to the metasurface. We find the largest second-harmonic generation efficiency for the resonance dominated by the electric contributions because its specific field distribution enables the most efficient usage of the largest element of the lithium niobate nonlinear susceptibility tensor. This is confirmed by polarization-resolved second-harmonic measurements, where we study contributions from different elements of the nonlinear susceptibility tensor to the total second-harmonic signal. Our work facilitates establishing lithium niobate as a material for resonant nanophotonics.